Retrospective study of gunshot wounds in the face in a large hospital in Latin America: a two-year analysis - Leone, Caroline; de-Campos, Wladimir Gushiken; Silva, Vinícius Teixeira; Rocha, Glauber Bareia; Cecchetti, Marcelo Minharro; Lemos, Celso Augusto (Journal of Oral Diagnosis, 2022)
Objective: This study aims to compare data relating to gender, age, etiology, fractured areas, procedures performed, follow-up and purpose from September 2013 to July 2015. This retrospective study included patients whose medical records were complete and who presented face fractures due to gunshot wounds. Results: A total of 1289 patients diagnosed with fractures in the head and neck region were evaluated, of which only 13 patients had facial fractures caused by firearms. Stabilization of facial fractures with rigid internal fixation should be performed as soon as possible to avoid sequelae to the patient, which was conduc- ted in 8 patients. Conclusions: The study found that male and young patients are the most affected by fire injuries to the face due to the high rate of violence, cultural and socioeconomic differences in the city of São Paulo. Fracture stabilization must be performed as soon as possible to avoid future sequelae. Therefore, the study found that the care of facial trauma by firearm does not have a strict protocol; it depends on the extent and severity of each case.